Impact of Wastewater and Canal Water Irrigation on the Accumulation of Copper in Maize and Millet of Different Districts of Punjab Pakistan - Ifra Saleem Malik (Journal of Bioresource Management, 2021)
In current work, we examined the absorption of metal Copper in generally grown food crops (Maize & Millet), cultivated in the waste water irrigated different Districts of Punjab, Pakistan. Analyzed samples of Water, Soil, shoot and grain were processed through atomic absorption spectrometric method. Our findings of Copper in water and Shoot were highest for Millet of Sargodha, irrigated with wastewater (1.69 mg/kg and 1.43 mg/kg respectively). In soil and grain samples maximum absorption of Cu was obtained in the waste water irrigated Maize (Sargodha) and Millet (Sheikhupura). Overall, Cu level was within the acceptable parameters set by FAO/WHO (2001). In this study, we also find out different indices such as Enrichment factor, Translocation factor, Pollution Load Index, Bio-concentration factor, Daily intake of metal and Health Risk Index. The study determined that frequently intake of waste watered forages in experimenting zone may carry possible health uncertainties in inhabitants.